2022
DOI: 10.3390/ijerph192114592
|View full text |Cite
|
Sign up to set email alerts
|

Association of Long Noncoding RNA HOTAIR Polymorphism and the Clinical Manifestations of Diabetic Retinopathy

Abstract: The aim of the current study is to evaluate the possible correlation between the single-nucleotide polymorphisms (SNP) of HOX transcript antisense intergenic RNA (HOTAIR) and the clinical characteristics of diabetic retinopathy (DR). Four loci of HOTAIR SNPs, including rs920778 (T/C), rs12427129 (C/T), rs4759314 (A/G), and rs1899663 (G/T), were genotyped via the TaqMan allelic discrimination for 276 DR individuals and 452 non-DR patients. The distribution frequency of HOTAIR SNP rs12427129 CT [adjusted odds ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…In addition, significant upregulation of rs1899663-TT and rs12427129-CT + TT SNPs were observed in patients diagnosed with proliferative diabetic retinopathy (Ref. 56).…”
Section: Diabetic Retinopathy and Neuropathymentioning
confidence: 99%
“…In addition, significant upregulation of rs1899663-TT and rs12427129-CT + TT SNPs were observed in patients diagnosed with proliferative diabetic retinopathy (Ref. 56).…”
Section: Diabetic Retinopathy and Neuropathymentioning
confidence: 99%
“…Clinical data have also illustrated the probable linkages of HOTAIR SNPs in diabetic retinopathy. In a case–control study by Chuang et al ( 2022 ) involving subjects with diabetic retinopathy and controls, SNPs rs12427129-CT, rs12427129-CT + TT, and rs1899663-TT were reported to have aberrantly upregulated expression in diabetic retinopathy patients. Moreover, significantly increased presence of SNPs rs12427129-CT + TT and rs1899663-TT were confirmed in clinical subjects of proliferative diabetic retinopathy (Chuang et al 2022 ).…”
Section: Hotair In Non-oncological Brain Pathophysiological ...mentioning
confidence: 99%
“…There are some factors that affect the development and progression of DR. A higher glycated hemoglobin (HbA1c) level, a longer duration of diabetes mellitus, hypertension, and dyslipidemia are associated with diabetic retinopathy (Cheung et al, 2010;Lin et al, 2021). Moreover, genetic factors play an essential role in DR, and genetic studies show a racial variation in DR's incidence (Simó-Servat et al, 2013;Cho and Sobrin, 2014;Mankoč Ramuš et al, 2021;Chuang et al, 2022a;Chuang et al, 2022b;Lee et al, 2022). Genome-wide analysis of DNA methylation in patients with type 1 diabetes mellitus found that this is associated with PDR (Agardh et al, 2015).…”
Section: Introductionmentioning
confidence: 99%